Standardization as Multifunctional Tool to Improve the Effectiveness of Analytical Procedures - E. B. Gerasimova (Учёт. Анализ. Аудит)
Modern social and economic conditions require the development of new approaches to the organization and analysis of an economic entity performance. The article pays special attention to the system of analytical activities standardization in order to meet the information needs of stakeholders. The objective of the study is the author’s development of the system of standardization of the economic entity performance analysis. The methods of system research (analysis and synthesis), comparative analysis, and the method of analogies are used to solve the problems. The study is based on the study of current economic literature and the use of structural analysis. The following results are obtained on the basis of the analysis. First, the special features of analytical procedures as an object of standardization were identified. These features are the starting point to develop a system of economic analysis standardization. Second, the algorithm of standardization of management activities was formulated. This algorithm is a basis to build a system of economic analysis standards. Third, a model of interaction between the main groups of stakeholders and the economic entity in terms of analytical activity standardization is proposed and the need to standardize the analysis of financial and nonfinancial characteristics of business quality of the object under analysis is proved. Fourth, the process of analytical activities standardization is developed. The system of indicators to assess the quality of the system of standardization for analytical procedures is offered. The development of the standardization system of the business performance analysis is a very promising direction to improve the quality of business. Standardization of economic analysis opens up great opportunities to improve the quality of activities of economic entities, regardless of the specific scope of the evaluation study.